A Comparison of the oxygenating differences of invasive non-native Lagarosiphon major and native Ceratophyllum demersum. (31st October 2018) - Mitchell-Holland, Rhiann; Morris, Nicola Jane; McGregor, Peter Kenneth
Abstract: Native to Southern Africa, Lagarosiphon majo r is a submerged macrophyte that is recognized as a problematic, invasive non-native species in many countries including the UK. It is widely sold and promoted through the aquarium and water garden industry as an 'efficient oxygenator' for freshwater systems, irrespective of the absence of evidence to support this statement and evidence of its adverse ecological and economic impacts. A key concern, relating to its rapid growth rate and high fresh weight density, is that L. major can impose self-shading and limitation of photosynthetic and respiratory activity, causing it to consume more oxygen than it produces. Low dissolved oxygen (DO) conditions typify diminished water quality and seriously limit oxygen-dependent organisms. We measured over several months the DO, fresh weight and associated pond life abundances of L. major and a comparable UK-native macrophyte, Ceratophyllum demersum, established in small-pond conditions to determine which species best maintained a healthy freshwater environment. Both the time from establishment and species had significant effects on DO concentrations and pond life abundance; L. major produced the least amount of oxygen over time and had significantly less associated pond life compared to the native plant. L. major also increased significantly in overall fresh weight compared to C. demersum, indicating the higher invasive ability of the non-native species. In conclusion, our results suggest that L. major is not as good an oxygenator as C. demersum and that this native species should be promoted through the aquarium and water garden trades as an efficient oxygenator that improves water quality and habitat conditions over time.